Tingkat Ergonomi Kursi dan Meja Berkorelasi dengan Tingkat Kelelahan Siswa di Sekolah Dasar Negeri Pujokusuman 1 Kota Yogyakarta - Novita Anggarini; Agus Suwarni; Abdul Hadi Kadarusno (Poltekkes Kemenkes Yogyakarta, 2015)
Unergonomic chairs and desks are caused from a mismatch with anthropometric measurement of students’ body. The impact of this condition make the students feel fatigue quickly and if lasts for longer duration, it will lead to changes in posture and impaired growth and therefore will lead to disruption in the learning process. The purpose of this study was to determine the correlation between the ergonomic level of chairs and desks and fatigue level of students at Pujokusuman 1 Primary School in Yogyakarta City by conducting a cross sectional designed survey. The respondents who were selected following systematic sampling technique was 56 Grade IV students.The results shows that only 19,64 % chairs and desks are ergonomic and 73,21 % students hadexperienced fatigue. Chi square statistical test results at level of significane or ? 0,05; obtained ap value of 0,005 which means that ergonomic level of chairs and desks correlates significantlywith fatigue level of respondents, i.e. students who use ergonomic chairs and desks have lowerfatigue level compared with those who use the unergonomic ones.